Effect of salinity on water stress, growth and yield of broadbean - Katerji N.; van Hoorn I.W.; Hamdy A.; Bouzid N.; El Sayed Mahrous S.; Mastrorilli M. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
Broadbeans were grown on clay in tanks and irrigated with water of three different levels of salinity. During the experiment, soil salinity, determined from the salt balance and soil water samples, showed a gradual increase. The water stress of the broadbeans was determined by measuring the predawn leaf water potential, the stomatal conductance and the differences in radiation temperature between the treatments. Growth was measured as leaf area and dry-matter production and, finally, the yield and its components were determined. The three water stress parameters and the two growth parameters showed good coherence, with all parameters indicating systematic differences between the saline treatments and the control. At increasing salinity water potential of the leaf and the stomatal conductance decreased, the difference in radiation temperature increased, and the leaf area, dry matter production and yield were reduced.